2023
DOI: 10.3390/cryst13020352
|View full text |Cite
|
Sign up to set email alerts
|

Textile Functionalization by Porous Protein Crystal Conjugation and Guest Molecule Loading

Abstract: Protein crystals are versatile nanostructured materials that can be readily engineered for applications in nanomedicine and nanobiotechnology. Despite their versatility, the small size of typical individual protein crystals (less than one cubic mm) presents challenges for macroscale applications. One way to overcome this limitation is by immobilizing protein crystals onto larger substrates. Cotton is composed primarily of cellulose, the most common natural fiber in the world, and is routinely used in numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In pursuit of multifunctional textiles involving attachment of protein crystal depots, Hartje et al from our group recently demonstrated integration of individual lysozyme and CJ crystals on bulk cotton, via chemical cross-linking with dihydrazides or dialdehydes, respectively. 194 The resulting crystals were able to adsorb guest sulforhodamine-labeled cytochrome P450 protein, although the activity of guest P450 enzyme was not tested. Despite repeated laundering of the functionalized fabrics, at least 20% of the attached crystals were retained when chemically cross-linked to fabric.…”
Section: Emerging and Future Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In pursuit of multifunctional textiles involving attachment of protein crystal depots, Hartje et al from our group recently demonstrated integration of individual lysozyme and CJ crystals on bulk cotton, via chemical cross-linking with dihydrazides or dialdehydes, respectively. 194 The resulting crystals were able to adsorb guest sulforhodamine-labeled cytochrome P450 protein, although the activity of guest P450 enzyme was not tested. Despite repeated laundering of the functionalized fabrics, at least 20% of the attached crystals were retained when chemically cross-linked to fabric.…”
Section: Emerging and Future Applicationsmentioning
confidence: 99%
“…Despite repeated laundering of the functionalized fabrics, at least 20% of the attached crystals were retained when chemically cross-linked to fabric. 194 The authors suggest that journal is © The Royal Society of Chemistry 2024 crystal retention might be improved via more robust chemical crosslinking; 194 additional strategies could involve in situ crystal growth on the surface of the fabric, which could reduce downstream handling and transfer of crystals. This approach may enable additional functionalization of cloth surfaces, particularly when combined with biosensing crystals or scaffolds which interact with specific pathogens.…”
Section: Emerging and Future Applicationsmentioning
confidence: 99%